2003
DOI: 10.1007/bf03018740
|View full text |Cite
|
Sign up to set email alerts
|

Severe fetal bradycardia in a pregnant surgical patient despite normal oxygénation and blood pressure

Abstract: P Pu ur rp po os se e: : To report and discuss a case of fetal bradycardia in a parturient under anesthesia for cholecystectomy despite normal maternal oxygenation and arterial blood pressure.C Cl li in ni ic ca al l f fe ea at tu ur re es s: : A 27-yr-old woman (gravida 2 para 1), with a fetus of 34 weeks gestation, received general anesthesia for cholecystectomy. After anesthesia induction and tracheal intubation, anesthesia was maintained with oxygen, sevoflurane and iv remifentanil infusion. While preparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 14 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…12,13 Others have described the need for naloxone at birth, 14 neonatal chest wall rigidity, 15 and severe fetal bradycardia. 16 A recent study showed that a bolus dose of 1 µg·kg -1 of remifentanil, during induction of general anesthesia for Cesarean delivery, blunts maternal cardiovascular effects of intubation, but may cause neonatal depression. 17 We ensured that a neonatal team was present to resuscitate the baby, if required.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Others have described the need for naloxone at birth, 14 neonatal chest wall rigidity, 15 and severe fetal bradycardia. 16 A recent study showed that a bolus dose of 1 µg·kg -1 of remifentanil, during induction of general anesthesia for Cesarean delivery, blunts maternal cardiovascular effects of intubation, but may cause neonatal depression. 17 We ensured that a neonatal team was present to resuscitate the baby, if required.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data about remifentanil hazards; they are reported mostly in pediatric patients [13,15,16]. In our case, the patient was hemodynamically stable without signs of muscle rigidity.…”
Section: Discussionmentioning
confidence: 58%
“…The combination of increased vascular resistance from the tightly coiled state and further external compression may cause marked reduction of the umbilical circulation. Impaired umbilical blood flow may lead to fetal hypoxia even if the maternal oxygenation and circulation are normal [12]. Liu et al [13] reported on five patients who demonstrated loss of variability following induction of anesthesia, with two of the five demonstrating a reduction in the baseline FHR with no detectable maternal changes.…”
Section: Discussionmentioning
confidence: 98%